2021
DOI: 10.1016/s2542-5196(21)00113-3
|View full text |Cite
|
Sign up to set email alerts
|

Framing climate change as a human health issue: enough to tip the scale in climate policy?

Abstract: Almost four decades of climate science have not yet led to transformative policy change at the pace and scale required to confront the climate crisis. Colleagues in the planetary health community attribute much potential to framing climate change as human health issue in order to create greater impact on policy makers. In this Personal View, we discuss the promise and limitations of this approach by drawing on insights from political science and public policy with regards to the complexity of these contentious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…However, as in studies with other hospital stakeholder groups, it appeared that beneficence through mitigating climate change was seen as subordinate priority compared with beneficence through immediate patient care 14–16. In the hospital context, as our study showed, there is often a significant concern about harming patients, while in the general context, mitigation measures predominantly raise concerns about limited personal freedom and imposed financial burdens 38. Results from a study comparing per capita GHG emissions from the health sector in different US states indicate that reduced GHG emissions do not compromise the quality of health systems 39.…”
Section: Discussionsupporting
confidence: 54%
“…However, as in studies with other hospital stakeholder groups, it appeared that beneficence through mitigating climate change was seen as subordinate priority compared with beneficence through immediate patient care 14–16. In the hospital context, as our study showed, there is often a significant concern about harming patients, while in the general context, mitigation measures predominantly raise concerns about limited personal freedom and imposed financial burdens 38. Results from a study comparing per capita GHG emissions from the health sector in different US states indicate that reduced GHG emissions do not compromise the quality of health systems 39.…”
Section: Discussionsupporting
confidence: 54%
“…Thus, adverse effects will reverberate across the human lifespan, with individuals born disadvantaged from in utero climate insults, burdened with predispositions to disease (e.g. obesity, metabolic disorders, congenital defects, allergies, neurodevelopmental and psychological impairments, etc), and ill‐adapted to further climate insults during their own lifetimes 87,108 …”
Section: Discussionmentioning
confidence: 99%
“…obesity, metabolic disorders, congenital defects, allergies, neurodevelopmental and psychological impairments, etc), and illadapted to further climate insults during their own lifetimes. 87,108 It is also clear that the health of women is affected disproportionately due to the climate crisis, although they contribute little to its genesis. In protecting pregnant women and the developing fetus from the health hazards associated with air pollution, heat, and natural disasters, any individual efforts-while commendable-are insufficient and beyond individual control due to the systematic sources of the climate change problem, of which the fossil fuel industry is an important contributor.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…Portraying the human health impacts of major climate hazards such as EWEs has been seen as a compelling way to foster climate action 2 . EWEs shock and resonate with people 3 , and a health frame may help to convince the public and decision-makers of their self-interest in proactive climate policy 2,4 . Among elements of this health framing, the World Health Organization (WHO) has called the 2015 Paris Agreement "potentially the most important public health agreement of the century" 5 , while the Lancet Countdown on Health and Climate Change annually monitors and disseminates health and climate indicators, including those associated with EWEs such as heatwaves and wildfires 2 .…”
mentioning
confidence: 99%
“…Arguably, the public health frame helped to achieve this modest progress 7,9 . Yet, observers have wondered if the health frame is sufficient to motivate people and policymakers to greater ambition 4 .…”
mentioning
confidence: 99%